Estudo de substâncias com efeito de regulador de crescimento no potencial fisiológico do arroz irrigado - Grohs, Mara (2012)
The objective of this study was to evaluate the interference of substances with effect of growth regulator, applied to seeds in physiological quality of rice seed subjected to the condition of low temperature stress, seeking to identify the enzymatic mechanism of action of these products, well as their performance on the field, on different sowing dates and cropping systems. For this reason, various experiments were conducted at the experimental of field and in the laboratory using the phytohormone gibberellic acid, the insecticide thiamethoxam and an organo-mineral fertilizer, Haf Plus®. In general, the products tested increased the germination end of most rice cultivars, and their efficiency linked to the existence of low temperature, with greater emphasis on the gibberellic acid, which also influence the final germination, increases seed germination. In cold-sensitive cultivars, as Irga 424, there is no influence of the products in the physiological. The products act beneficially on the antioxidant system of plants, mainly on the activity of superoxide dismutase, reducing free radical production and lipid peroxidation. However, the difference in vigour between the samples were not sufficiently large so that manifest themselves in the field, for the establishment of the crop. As environmental conditions become less favorable, as in an early planting season or in the conventional tillage is a major contribution of the products on the agronomic performance, not reflecting, however, on yield.